2006
DOI: 10.1086/509872
|View full text |Cite
|
Sign up to set email alerts
|

A Young Stellar Cluster Surrounding the Peculiar Eruptive Variable V838 Monocerotis

Abstract: V838 Monocerotis is an unusual variable star that underwent a sudden outburst in 2002. Unlike a classical nova, which quickly evolves to high temperatures, V838 Mon remained an extremely cool, luminous supergiant throughout its eruption. It continues to illuminate a spectacular series of light echoes, as the outburst light is scattered from nearby circumstellar dust. V838 Mon has an unresolved B3 V companion star.During a program of spectroscopic monitoring of V838 Mon, we serendipitously discovered that a nei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 26 publications
(24 reference statements)
2
59
0
Order By: Relevance
“…Below we investigate its origin in more depth. V838 Mon is a member of a group of hot stars, which includes three stars of spectral types B3-6 and the B3 companion of V838 Mon (Afşar & Bond 2007). All of these stars are seen within the echoing region of the sky but well outside the region of the main molecular emission.…”
Section: Discussion: the Origin Of The Echo Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Below we investigate its origin in more depth. V838 Mon is a member of a group of hot stars, which includes three stars of spectral types B3-6 and the B3 companion of V838 Mon (Afşar & Bond 2007). All of these stars are seen within the echoing region of the sky but well outside the region of the main molecular emission.…”
Section: Discussion: the Origin Of The Echo Materialsmentioning
confidence: 99%
“…Afşar & Bond (2007) constrained the age of the cluster to be younger than 25 Myr. Our result is consistent with their constraint, but suggests that an even younger age is more probable.…”
Section: Discussion: the Origin Of The Echo Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider the following (possibly overlapping) hypotheses for the nature of SN2010da: an SN2008S-like transient, an outburst from an LBV/sgB[e]-HMXB, a presumed stellar merger event like V1309Sco (Tylenda et al 2011),V838Mon (Bond et al 2003, Afşar & Bond 2007)or the recently identified NGC 4490-OT (Smith et al 2016), or a low-luminosity supernova explosion (e.g., electron-capture).…”
Section: On the Nature Of Sn2010damentioning
confidence: 99%